Growth Performance and Mapping of Forest Productivity: An Analysis of Indian States - Singh, Jagdeep; Singh, Nirmal; Kapoor, Shilpi; Banoo, Saira (Indian Forester, 2022)
Forests are a precious gift of nature to human for their livelihood. The forest transition narrates the reversal of land use trends during the critical period from loss in net area under forest to the net gain in the long run. Despite the importance of forests for human beings, forests have been lagging behind in terms of income and employment generation in India. This paper aims to study the changing contribution and growth performance of forest sector in India. The study is based on secondary data collected from CSO and DES. In case of forest productivity (Gross Value Added per hector), the long-term growth trend was found to be in cyclical pattern. In the recent time starting from decade ending 2011-12 there is increasing trend cycle. It is also found that the growth trend of productivity of the sector was between -2 per cent and 1.8 per cent in the recent phase. It is around no change level in the recent decade. Downward slope of the fitted curve shows the convergence of productivity. But the rate of caching-up is not significant. The forestry model which is based on community can be useful for improving opportunities of livelihood and conservation.